2020
DOI: 10.3126/researcher.v4i1.33816
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting Techniques on Rationalize Decisions in the Nepalese Listed Manufacturing Companies

Abstract: The objective of this study was to examine how much the Nepalese listed manufacturing companies are utilizing management accounting techniques to rationalize decisions. It followed a descriptive research design and employed a survey questionnaire instrument to collect data. The population of this study comprised all the listed manufacturing companies on the Nepal Stock Exchange and their employees. Targeted respondents were those representatives of the sample companies who worked in the accounting department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Studies on the effects of management accounting on financial performance have been accumulated for for-profit firms (Alamri, 2019;Dahal et al, 2020;Onodi et al, 2021). For example, Alamri (2019) found that the introduction of activity based costing alone does not improve return on investment, but only in firms that perform more complex operations and use activity based costing in conjunction with other management systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on the effects of management accounting on financial performance have been accumulated for for-profit firms (Alamri, 2019;Dahal et al, 2020;Onodi et al, 2021). For example, Alamri (2019) found that the introduction of activity based costing alone does not improve return on investment, but only in firms that perform more complex operations and use activity based costing in conjunction with other management systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the review concerning MAPs led in the world is on manufacturing firms. However, studies of efficacious organizations have featured the capability of MA information as a strategic weapon (Dahal, 2021a). MAPs assist executives in serving customer needs, accelerating decision-making processes, and managing the corporate value chain (Dahal, 2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Managerial decisions (MDs) emphasize managers' engagement in leveraging external information resources by providing the knowledge necessary to create practical competencies for fully utilizing internal organizational resources (Knight & Collier, 2009). Managers' performance is inextricably concerned with MA procedures, which might contribute to managers making necessary modifications and revisions to ensure operative and successful MDs (Abrahman et al, 2016;Dahal et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, management accounting has focused on annual controls in secure and confirmed competitive operating environments due to the managers' need for historical data to apprehend overall performance and manipulate accountability in their organization (Taipaleenmaki & Ikaheimo, 2013). Management accounting's ongoing fashion has shifted from history-based planning and control to future-oriented decisions, strategic planning, and control (Dahal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%